The development of post traumatic stress disorder among secondary school students in borno state Nigeria: a systematic review - Abu Bakar, Zainudin; Kabiru Rabiu, Darma (International Journal of Engineering and Technology, 2018)
Insurgency has long been rooted in the Nigerian society. It affected deeply in the daily activities of the country. Thousands of people including school children have been maimed, displaced, orphaned and killed in Borno and entire North Eastern Nigeria and some other part of North Western Nigeria especially in the state of Kano because of the insurgency. The Boko Haram movement for example have caused enormous chaos within the society especially the school children. The movement have targeted civilian populations irrespective of gender, tribal and religious inclination among people and, the merciless attack and bombings carried out by them including abduction and kidnapping of female students have caused destruction of the school facilities and the well-being of the society. A continuous exposure to such stress created by war resulted the development various difficulties such as Post-Traumatic Stress Disorder among school children. A systematic review was used to critically analyzed the impact of the insurgency in the society based on several related studies. The effect of the insurgency on the society was then highlighted which tells the story of the educational difficulties. Â